The Temporal Change of Cortical Activation Induced by the Ongoing Effects of Transcranial Direct Current Stimulation - Lee, Mi Young; Park, Ji Won; Nam, Ki Seok; Jang, Sung Ho; Kwon, Yong Hyun (Journal of Physical Therapy Science, 2011)
[Purpose] The aim of this study was to determine when cortical activation of targeted neurons is induced by the ongoing effects of anodal transcranial direct current stimulation (tDCS), and how temporal change is processed, using functional magnetic resonance image (fMRI). [Subjects and Methods] Eleven healthy right-handed subjects were recruited. Functional MRI was performed for five consecutive 1-minute phases (control, tDCS1, tDCS2, tDCS3, tDCS4). During four tDCS phases, direct current with 1.0 mA was delivered to the hand knob of the precentral gyrus, and the resting phase served as a control session. [Results] Our findings show that cortical neurons below the anodal tDCS were activated from the second through the fourth tDCS phase. However, there was no activation in the first tDCS phase. In addition, the amount of cortical activation (peak voxels) tended to fluctuate from the second phase through fourth phases. [Conclusion] We demonstrated that the a continuous effect of tDCS was induced after 1 minute since the direct current is injected to target neurons. The effect was maintained during the application tDCS, although it fluctuated.